Internationalization of Higher Education (HE) in an Unequal Terrain: UDS and International Partnerships - Lobnibe, Jane-Frances Yirdong (American Journal of Social Sciences and Humanities, 2020)
The development of international partnerships for teaching and research has become one of the most significant strategies for internationalization among universities across the globe. For African universities, this practice is even more imperative in light of the African Union’s (AU) position that in order for Africa’s universities to play their critical role in development, they ‘will require partnerships not only with local and regional actors and stakeholders, but also with the universities, businesses and governments of the developed world’ (NEPAD (New Partnership for Africa’s Development), 2005). This paper examines the relations and nature of international partnerships as an expression of the internationalization of higher education in Ghanaian universities. Drawing on an analysis of partnership agreements between the University for Development Studies (UDS) and other institutions and interviews with partnership program officers and students, it argues that partnerships in higher education as often captured in the MOUs present enormous benefits in program design, implementation and outcomes, but that institutions in developing countries like UDS are often not equipped in terms of the structural arrangements to engage on equal footing with their partner institutions from the global north in order to maximize the intended mutual benefits they bring.